ANALYSIS OF THE IMPLEMENTATION OF THE PANCASILA DIMENSIONAL STUDENT PROFILE (FAITH, DELIBERATION TO THE ALMIGHTY GOD AND NOBLE IMAGES) AT MTSN 1 KERINCI - Qutrul Nada, Fitria; Pandapotan Simaremare, Tohap; Utami, Sundari (EDU RESEARCH, 2025)
The background to this research reveals the problems that occur at MTsN 1 Kerinci, where the Pancasila Student Profile program has not been fully implemented and is still less visible in practice. Most teachers experience difficulties in organizing appropriate activities, especially in aligning the implementation of the Pancasila Student Profile with effective and relevant projects or activities to support these values.This research aims to analyze the implementation and inhibiting factors in implementing the dimensions of Faith, Fear of God Almighty, and Noble Character in the Pancasila Student Profile. This research was conducted at MTsN 1 Kerinci, Air Hangat Timur District, Kerinci Regency. Data collection techniques used include observation, interviews and documentation. The implementation of the values ​​of being devoted to God Almighty and having noble morals has been effective. In the P5 Program, teachers act as planners, facilitators, companions, supervisors and moderators. As part of the implementation of the P5 Teaching Module with the theme "Dhuha Prayer," this program was designed and implemented with the support of worship facilities and teacher guidance in carrying out the Dhuha Prayer in congregation and reflection on faith. Teachers also regularly supervise and guide students, while facilitating scheduled discussions to deepen their understanding of religious values. However, there are still several obstacles in its implementation, such as a lack of understanding by some teachers regarding the P5 concept, limited references to examples of comprehensive activity flows, and difficulties in aligning activity schedules with academic schedules. In addition, the high workload of teachers limits the time available to provide in-depth guidance, while the level of student activity in carrying out the program still needs to be increased. In conclusion, the implementation of the dimensions of the Pancasila Student Profile (Faith, Fear of God Almighty, and Noble Morals) has proceeded in accordance with the teacher's role in implementing P5. Teachers play a role in project planning, as well as carrying out functions as facilitators, companions, supervisors and moderators. However, in its implementation there are still several inhibiting factors that need to be overcome